The compressive performances of 3D-printed micron-size corrugated sandwich structures. (June 2023) - Ji, Lijun; Liu, Weilin; Gong, Wensheng; Qin, Xiang; Liu, Lingling; Luo, Liping
Micron-scale grid-shaped, V-shaped and U-shaped corrugated sandwich structures are fabricated by 3D printing technology and present different mechanical properties from those made by traditional method. Their peak stresses and elastic moduli could be fitted to cubic functions. The compression performance of the multilayer grid-shaped sandwich can be determined by the relative mechanical strength of layers. Adding a layer on a grid-shaped sandwich has no significant influence on the peak stress, but can enhance the elastic modulus by about 60.9 MPa. The deformation modes of multilayer V-shaped and U-shaped sandwiches can be determined by the load carrying path and the relative mechanical properties between interlayers and cores. The elastic modulus of V-shaped sandwich is enhanced with the increase of layer number, while the elastic modulus of U-shaped sandwich decreases with the increase of layer number. The peak stress and the elastic modulus of a four-layer V-shaped sandwich can reach 9.85 MPa and 261.09 MPa, and those of a four-layer U-shaped sandwich can reach 4.79 MPa and 119.18 MPa. The result reveals the principles that the reduced structural size and suppressed debonding, the structures and the load carrying path, and materials, influence the failure mode and mechanical properties of the corrugated sandwiches. Graphical Abstract